Parents' perceptions of oral health, general health and dental health care for children with Down syndrome in Sweden. (19th May 2021) - Stensson, M.; Norderyd, J.; Van Riper, M.; Marks, L.; Björk, M.
Abstract: Aim: To describe parental perceptions of general health, oral health and received dental health care in Swedish children with Down syndrome (DS). Methods: Online questionnaire, quantitative data analysis (Chi-square test). Results: Parents of 101 children with DS (52 boys, 49 girls, mean age: 9.6 years) participated. Seventy percent rated their child's general health and 74% their child's oral health as good or very good. Parents, who rated their child's oral health as poor (8%), also reported that dental procedures were difficult. Children received dental care at general (55%) and specialist clinics (53%). Ninety-four percent of parents of children receiving specialist dental health care were satisfied compared to 70% of parents with children in general clinics. The parents most valued characteristics of dental professionals were patience (63%) and their ability to engage the child (68%). Parents wanted multidisciplinary collaboration. Conclusion: Most parents rated their child's general and oral health as good or very good. Children with poor oral health were also reported to have difficulties coping with dental procedures. Parents wanted dental care to be tailored to meet their child's unique needs. They wanted dental professionals to have knowledge about children with a need for special care. Lastly, they requested multidisciplinary collaboration.